2016
DOI: 10.1098/rspb.2016.1201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiological stress and behaviour in semi-free-ranging red-capped mangabeys ( Cercocebus torquatus ) following antiparasitic treatment

Abstract: Parasites are ubiquitous in wildlife populations, but physiological and behavioural responses of hosts to infection are difficult to measure. We experimentally treated semi-free-ranging red-capped mangabeys (Cercocebus torquatus) in Nigeria with antiparasitic drugs and examined subsequent changes in glucocorticoid production and individual behaviour. Because both parasites and stress impact energy balance and health, we measured (i) behavioural time re-allocation via activity budgets, (ii) social relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
(93 reference statements)
3
15
0
Order By: Relevance
“…First, in support of the idea that glucocorticoids are associated with immunosuppression ( Nava-Castro et al, 2011 ), we found that females with high fecal glucocorticoid concentrations harbored high quantities of Trichuris eggs. This result is consistent with other studies of nonhuman primates that have also found positive correlations between glucocorticoid concentrations and helminth parasite loads (e.g., red colobus monkey, Procolobus rufomitratus : Chapman et al, 2006 ; red-capped mangabey, Cercocebus torquatus : Friant et al, 2016 ; yellow baboon, P. cynocephalus : Akinyi et al, 2019 ; Barbary macaque, Macaca sylvanus : Müller-Klein et al, 2019 ). However, contrary to this result, we also found that females with high fecal glucocorticoid concentrations were at low risk of Oesophagostomum infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, in support of the idea that glucocorticoids are associated with immunosuppression ( Nava-Castro et al, 2011 ), we found that females with high fecal glucocorticoid concentrations harbored high quantities of Trichuris eggs. This result is consistent with other studies of nonhuman primates that have also found positive correlations between glucocorticoid concentrations and helminth parasite loads (e.g., red colobus monkey, Procolobus rufomitratus : Chapman et al, 2006 ; red-capped mangabey, Cercocebus torquatus : Friant et al, 2016 ; yellow baboon, P. cynocephalus : Akinyi et al, 2019 ; Barbary macaque, Macaca sylvanus : Müller-Klein et al, 2019 ). However, contrary to this result, we also found that females with high fecal glucocorticoid concentrations were at low risk of Oesophagostomum infection.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we found that baboon hosts are especially sensitive to parasitism during the costliest phases of the reproductive cycle: pregnancy and lactation. Moreover, while most studies of wild animals have focused on the relationship between glucocorticoid concentrations and parasitism (e.g., Friant et al, 2016 ; Akinyi et al, 2019 ; Müller-Klein et al, 2019 ), our study supplements this body of literature by additionally testing the association between sex hormones (progesterone and estrogen) and parasitism. Interestingly, our findings reveal that the interaction between sex hormones, reproductive state, and parasite infection is quite complex, and that baboon hosts are differentially vulnerable to different genera of parasites, which suggests that individual characteristics of parasites and different hormonal and reproductive environments of the host mediate the course of infection.…”
Section: Discussionmentioning
confidence: 95%
“…The physiological costs associated with helminth infection may be reflected in hormones that indicate host energetic expenditure, such as glucocorticoids (GCs). Several studies, both experimental and observational in the wild, have found significant positive correlations between host GC levels and patterns of helminth infection (Friant, Ziegler, & Goldberg, 2016;Muehlenbein & Watts, 2010;Müller-Klein et al, 2018;Sures, Knopf, & Kloas, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted April 22, 2021. ; https://doi.org/10.1101/2021.04. 22.440985 doi: bioRxiv preprint It has long been established that pathogens with high fatality rates, such as epidemic viruses, can drive population declines, and may contribute to local extinctions [1]. The effects of sub-clinical or non-lethal infections are often overlooked, however, despite costs to host health and fitness, and the consequent impact of such diseases on population viability [2].…”
Section: Introductionmentioning
confidence: 99%